INTERNAL FACTOR ANALYSIS AND BUSINESS PLANNING RISK MANAGEMENT OF PT. BHAKTI LELANG INDONESIA - Pramono, Hendrio; Syah, Tantry Yanuar; Negoro, Dimas Angga; Iskandar, Muhammad Dhafi (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
PT Bhakti Lelang Indonesia (BIDKU) is an entity in the automotive auction industry with a special plan to hold auctions for two-wheeled and four-wheeled vehicles, which is planned to be established in 2025. BIDKU aims to build a reputation as one of the leading auction houses in Indonesia. As a major player in the automotive auction industry, BIDKU regularly holds auctions that provide opportunities for various parties, including companies and individuals, to participate in the auction process. BIDKU provides a platform that ensures easy and safe access to purchase quality vehicles at competitive prices. The transparent and professional auction process ensures a satisfying experience for each participant, with a commitment to maintaining integrity and ethics at every stage of the auction, thus building customer trust. With branch locations spread throughout Indonesia and two regional offices in Tangerang for Western Indonesia and Surabaya for Eastern Indonesia, BIDKU plans to hold auctions regularly in various regions, facilitating participation for buyers and sellers in both online and hybrid formats. BIDKU has the ambition to have more than 50,000 registered participants in its auction process. BIDKU plans to partner with more than 350 used vehicle dealers and 250 companies to hold vehicle auctions under the BIDKU banner